Optical properties of the poly(N-benzylaniline) thin film - Arslan, M; Duymus, H; Yakuphanoğlu, Fahrettin (Amer Chemical Soc, 2006)
The optical properties of the poly (N-benzylaniline) thin film were investigated by optical characterization. The optical constants such as refractive index and dielectric constant were determined from the transmittance and reflectance spectra of the film. The refractive index dispersion was analyzed by the Wemple-DiDomenico model. The n(infinity) values changed from 6.37 to 5.71 and these values did not show any certain trend with annealing temperatures. The average oscillator parameter S,, value, which is the strength of the individual dipole oscillator, was found to be in the range of 1.15 x 10(13) to 1.03 x 10(13) m(-2). The optical band was determined from the direct optical transitions in K space. The optical band E, of the film decreases from 2.089 to 2.046 eV with increasing annealing temperatures while the Urbach energy E-u called the width of localized states in the optical band gap increases from 0.544 to 0.598 eV. Consequently, the optical constants and optical band gap of the poly(N-benzylaniline) change with the annealing temperatures.
Keywords: Polyaniline; Constants; Complex; Growth